Biodiversity and epidemiology study of macroparasites from stray cats in Peninsular Malaysia / Norhidayu binti Sahimin - Norhidayu, Sahimin (2012)
The occurrences of macroparasites from 543 stray cats were studied in four urban cities from west (Kuala Lumpur), east (Kuantan), north (Georgetown) and south (Malacca) of Peninsular Malaysia between May 2007 to August 2010. The hosts were infested with a minimum of one species and a maximum of six species of macroparasites. Of all four locations, Georgetown had the highest species diversity followed by Malacca, Kuala Lumpur and Kuantan. Five ectoparasites species were recovered namely, Ctenocephalides felis, Felicola subrostratus, Haemaphysalis bispinosa, Heterodoxus spiniger and Lynxacarus radovskyi. This study also recorded the dog louse, Heterodoxus spiniger for the first time in Malaysia from two cats in Georgetown. The cat fur mite, Lynxacarus radovskyi also reported for the first time on domestic cats from Peninsular Malaysia. Overall, species diversity of ectoparasites was low compared to previous studies. Similar infestations were observed between males and females meanwhile higher diversity of species richness was observed in adults compared to juveniles. Results showed no significant effect determining the ectoparasites distribution in stray cats population for any of the factors investigated.